2021
DOI: 10.5812/jjm.109512
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Haematological Analysis of Dengue Virus-3 Among Children in Lahore, Pakistan

Abstract: Background: Dengue virus (DENV) is an RNA virus belonging to the family Flaviviridae of the genus Flavivirus with worldwide distribution. Dengue fever is caused by any of four closely-related serotypes DENV, an emerging pandemic-prone viral disease in many regions of the world. Objectives: The present study aimed to determine the prevalence of dengue virus genotypes and serotypes in children aged below 15 years in Lahore, Pakistan. Methods: In this study, 112 serum samples were collected from clinically suspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…However, in the present study, DENV-3 (27.9%) was found to be the most prevalent serotype that causes DF and agree with many reports out of Sudan. There are many researches also conducted over the world and concluded that the DENV-3 was the leading serotype in Dehli, India, and Pakistan [19]. Furthermore, some reports showed that the DENV-1, DENV-2, and DENV-3 have been the predominant serotypes of DENV in the Middle East, particularly Saudi Arabia and Yemen [20].…”
Section: Resultsmentioning
confidence: 99%
“…However, in the present study, DENV-3 (27.9%) was found to be the most prevalent serotype that causes DF and agree with many reports out of Sudan. There are many researches also conducted over the world and concluded that the DENV-3 was the leading serotype in Dehli, India, and Pakistan [19]. Furthermore, some reports showed that the DENV-1, DENV-2, and DENV-3 have been the predominant serotypes of DENV in the Middle East, particularly Saudi Arabia and Yemen [20].…”
Section: Resultsmentioning
confidence: 99%
“…These states are near Uttarakhand and many locals travel in this state regularly which gives support to the theory of serotypes difference due to the travellers from different parts of the country. Studies from Indonesia and Pakistan reported that DEN-3 was dominant in children in 2014 and 2018, respectively[21,22]. However, in a study from Kenya during 2014-2017, all four serotypes were present in children, but the dominant serotype was DEN-2[23].…”
mentioning
confidence: 92%